2021
DOI: 10.1016/j.brs.2021.07.018
|View full text |Cite|
|
Sign up to set email alerts
|

Accelerated theta burst stimulation for the treatment of depression: A randomised controlled trial

Abstract: Introduction: Theta burst pattern repetitive transcranial magnetic stimulation (TBS) is increasingly applied to treat depression. TBS's brevity is well-suited to application in accelerated schedules. Sizeable trials of accelerated TBS are lacking; and optimal TBS parameters such as stimulation intensity are not established. Methods: We conducted a three arm, single blind, randomised, controlled, multi-site trial comparing accelerated bilateral TBS applied at 80 % or 120 % of the resting motor threshold and lef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
68
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 89 publications
4
68
0
Order By: Relevance
“…Further, the pattern of missing data is not discussed (monotonic, right censoring). For the treatment arms, the consort flow chart information on missing data is not consistent with the counts reported in table 4 [1].…”
mentioning
confidence: 89%
See 4 more Smart Citations
“…Further, the pattern of missing data is not discussed (monotonic, right censoring). For the treatment arms, the consort flow chart information on missing data is not consistent with the counts reported in table 4 [1].…”
mentioning
confidence: 89%
“…The authors reported that baseline demographic characteristics were similar across the three treatment arms; however, table 3 [1] shows higher count for female participants and antidepressants use (reads 35/75, 96/10 for low intensity treatment arm, respectively). The authors didn't report model-based marginal or conditional estimates/means for treatment effects, i.e.…”
mentioning
confidence: 97%
See 3 more Smart Citations